The Economic Determinants of the World Medical Tourism Industry Development - BAIEV, Vadim Victorovich; BAKHOV, Ivan Stepanovych; HOLOVACH, Nataliia Vasylivna; ZGALAT-LOZYNSKA, Liybov Oleksandrivna (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).22, 2020)
The paper considers the main types of medical tourism – diagnostic-therapeutic, health and beauty, and health resort treatment. It specifies the basic prerequisites for development of the international medical tourism industry – cost and quality of medical services, accreditation of medical institutions in compliance with international quality standards; development of medical tourism clusters.